2018
DOI: 10.1155/2018/2309108
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Expression of Skin Neurotrophic Factors in Advanced Diabetic Neuropathy Does Not Lead to Neural Regeneration despite Pancreas and Kidney Transplantation

Abstract: Diabetic peripheral neuropathy (DPN) is a common complication of diabetes with potential severe consequences. Its pathogenesis involves hyperglycemia-linked mechanisms, which may include changes in the expression of neurotrophic growth factors. We analyzed the expression of 29 factors potentially related to nerve degeneration and regeneration in skin biopsies from 13 type 1 diabetic pancreas and kidney recipients with severe DPN including severe depletion of intraepidermal nerve fibers (IENF) in lower limb ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Whereas some studies report a decrease in neutrophin levels ( Anand et al , 1996 ; Uceyler et al , 2015 ), others found increased levels ( Kennedy et al , 1998 ; Diemel et al , 1999 ) compared to healthy controls. Of note, a recent study reported higher levels of neurotrophin family mRNA in patients with diabetic neuropathy following pancreas/kidney transplantation compared to diabetic patients and healthy controls ( Saudek et al , 2018 ). In accordance with our findings however, serial skin evaluation before and after glucose homeostasis did not reveal changes in neurotrophin expression profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some studies report a decrease in neutrophin levels ( Anand et al , 1996 ; Uceyler et al , 2015 ), others found increased levels ( Kennedy et al , 1998 ; Diemel et al , 1999 ) compared to healthy controls. Of note, a recent study reported higher levels of neurotrophin family mRNA in patients with diabetic neuropathy following pancreas/kidney transplantation compared to diabetic patients and healthy controls ( Saudek et al , 2018 ). In accordance with our findings however, serial skin evaluation before and after glucose homeostasis did not reveal changes in neurotrophin expression profiles.…”
Section: Discussionmentioning
confidence: 99%
“…NGF synthesis is inhibited in the epidermis of diabetic mice, and NGF supplementation exacerbates neuropathic alterations in small fibers and autonomic disease [202]. Elevated levels of the neurotrophic elements did not result in a discernible regeneration of the peripheral sensory fibers in a study that investigated the expression of NGF and other factors in the skin following kidney and pancreas transplantation in individuals with DN [203]. These results demonstrate the urgent need to understand more about the cellular components of DN.…”
Section: Neurotrophic and Cellular Signalingmentioning
confidence: 89%
“…The interactions of BDNF and GDNF in nociceptive pathways impose a change of approach toward combinational therapies [246], including the delivery of both trophic factors and/or small molecules acting on downstream targets, aiming to restore an altered balance. On the other hand, the successful development of combinational therapies based on a homeostatic approach implies the availability of diagnostic tools to non-invasively explore the neurotrophic content at both central and peripheral levels in different types of painful neuropathies [247][248][249].…”
Section: Discussionmentioning
confidence: 99%